Dynamics and Challenges of National Insurance Law in the Context of Globalization - Putri Nawarni Harahap; Rizki Khoiril Waladi Siahaan; Siti Fatimah; Adi Syahputra; Fitri Elisa Noviani Simatupang (ISNU Sumatera Utara, 2025)
Globalization has driven cross-border openness in various sectors, including the insurance industry. In this context, Indonesia cannot close itself off the involvement of foreign parties in the implementation of the national insurance business. The existence of insurance companies basically aims to provide protection and solutions to the risks faced by the community, but the influx of foreign capital and companies gives rise to its own legal dynamics, especially related to company ownership, supervision, consumer protection, and national legal sovereignty. This research aims to analyze the dynamics and challenges of national insurance law in the face of globalization currents, especially in relation to foreign ownership regulation and the role of the state in safeguarding national interests. The research method used is normative legal research with a statutory and conceptual approach, through the study of insurance regulations and relevant legal doctrines. The results of the study show that globalization requires strengthening national insurance regulations in order to be able to increase the competitiveness of the domestic insurance industry without ignoring legal protection for the community. In addition, the government's role as a regulator and supervisor is crucial in creating legal certainty and public trust. In conclusion, harmonization between global openness and national legal interests is key in answering the challenges of insurance law in the era of globalization.